Nutritive value of the broiler litter based on sodium hidroxide treated rice straw and rice hulls for sheep - Barros, Nelson Nogueira; Bonnecarrere, Luiz Maria; Lopes, Juarez Marbini (Pesquisa Agropecuaria Brasileira, 2014)
Three levels (0, 6 and 12 percent) of NaOH treatment of rice straw and rice hull used as bedding on the nutritive value of broiler litter was studied in sheep. In the 2 x 3 factorial design, 18 sheep (3 in each of the groups) were used, digestibility of dry matter, organic matter, crude fibre and gross energy increased with increase of NaOH concentration on rice hull litter. For rice straw litter, reduction of these components was observed with the exception of crude fibre where increase in digestibility was observed with increase of NaOH from zero to 6 percent. Nitrogen digestibility of both litters decreased (P
Keywords: rice straw; rice hull; broiler litter